Reprodução bovina - Souza, Railson Silva (Universidade Federal do Tocantins, 2023)
This report describes the activities carried out and/or monitored during the Mandatory Supervised Curricular Internship, held from 03/07 to 05/16/2022, at the Center for Studies, Research and Extension in Genetics and Animal Improvement (NAPGEM) of the University Federal do Tocantins, together with core partner companies and veterinarians, under the supervision of Prof. Dr. Jorge Luís Ferreira and under the guidance of Prof. Dr. Maria de Jesus Veloso Soares, totaling a workload of 390 hours. The main activities developed during the internship were estrus synchronization in bovine females, puberty induction in heifers, FTAI (Fixed Time Artificial Insemination), pregnancy diagnosis through rectal palpation and ultrasound, as well as evaluation of artificial insemination results in fixed time in the properties served and surgeries in the field, such as cesarean sections, digit amputation, acrobustitis and aesthetic dehorning.